Transabdominal Pre-peritoneal Mesh Repair versus Lichtenstein’s Hernioplasty - Koju, Rajan; Koju, Ram Bhakta; Malla, Balaram; Dongol, Yashad; Thapa, Lok Bikram (Journal of Nepal Health Research Council, 2017)
Background: In the era of minimal invasive surgery, hernia repair has seen a paradigm shift from open to laparoscopic technique. However, superiority of laparoscopic repair over open repair is still controversial. Available literatures have shown laparoscopic technique to be better in term of post-operative pain and early return to work. Methods: In this prospective study, a total of 102 patients aged 21-78 years with inguinal hernia were recruited and enrolled into two comparative groups, namely Lichtenstein’s and Transabdominal pre-peritoneal, and each group containing 51 participants. Hospital ethical committee approval and written informed consent from patients was obtained. Primarily, the duration of operation, post-operative pain and complication, and quality of life after surgery was compared between the two different approaches of hernia repair. Results: The study results demonstrated a statistically significant superiority of trans abdominal pre-peritoneal repair over Lichtenstein’s hernioplasty in terms of post operative pain (2.00±0.63 vs 3.90±0.74 VAS score, P value<0.001), hospital stay (2.33±0.62 vs 2.96±0.20 days, P value <0.001) and quality of life with early return to normal work (13.39±0.60 vs 17.88±0.86 days, P value <0.001); whereas a prolonged operative time was seen in transabdominal pre-peritoneal repair (96.08±27.08 vs 42.55±5.95 mins, P value <0.001). Conclusions: This study has shown that transabdominal pre-peritoneal repair is better than Lichtenstein’s in respect to post-operative pain, quality of life and post-operative complication. However, it has prolonged operative duration than conventional method.